PENGUJIAN PUPUK HAYATI KALBAR UNTUK MENINGKATKAN PRODUKTIVITAS TANAMAN KEDELAI (Glycine max) var. BALURAN - Subowo, Yohanes Bernard; Sugiharto, Arwan; Suliasih, Suliasih; Widawati, Sri (Caraka Tani: Journal of Sustainable Agriculture, 2010)
Research aimed to evaluate the ability of kalbar biofertilizer to improve productivity of soybean. Experiment was conducted in the field experimental plot of Cibinong Science Centre. Soybean (Glycine max) var Baluran was treated with a series of fertilizer i.e.: compost containing Nitrogen fixing microbes, compost containing Phosphate solubilizing microbes, compost containing lignocelullosic degrading fungus, Kalbar biofertilizer (compost containing Nitrogen fixing, Phosphate solubilizing and lignocellulosic degrading microbes), chemist fertilizer, compost and control. The height of plant, fresh weight of biomass, number of leaves, pod number, and weight of seed were observed. The Nitrogen, Phosphate and Carbon which exist on the soil observed before planting, while flowering and while harvesting. The result was the application of kalbar biofertilizer able to increase the Carbon (C), Nitrogen (N) and Phosphor (P) content in the soil. This treatment also increased the fresh weight of biomass (22%), the number of pods (11, 11%) and the weight of seed (12,22%).